Cystatin C and Urine Albumin to Creatinine Ratio Predict 5-Year Mortality and Cardiovascular Events in People Living With HIV. (21st July 2020) - Chazot, Robin; Botelho-Nevers, Elisabeth; Mariat, Christophe; Frésard, Anne; Cavalier, Etienne; Lucht, Frédéric; Delanaye, Pierre; Maillard, Nicolas; Gagneux-Brunon, Amandine
Abstract: Background: Identifying people with HIV (PWH) at risk for chronic kidney disease, cardiovascular events, and death is crucial. We evaluated biomarkers to predict all-cause mortality and cardiovascular events, and measured glomerular filtration rate (mGFR) slope. Methods: Biomarkers were measured at enrollment. Baseline and 5-year mGFR were measured by plasma iohexol clearance. Outcomes were a composite criterion of all-cause mortality and/or cardiovascular events, and mGFR slope. Results: Of 168 subjects, 146 (87.4%) had undetectable HIV load. Median follow-up was 59.1 months (interquartile range, 56.2–62.1). At baseline, mean age was 49.5 years (± 9.8) and mean mGFR 98.9 mL/min/1.73m 2 (± 20.6). Seventeen deaths and 10 cardiovascular events occurred during 5-year follow-up. Baseline mGFR was not associated with mortality/cardiovascular events. In multivariable analysis, cystatin C (hazard ratio [HR], 5.978; 95% confidence interval [CI], 2.774–12.88; P < .0001) and urine albumin to creatinine ratio (uACR) at inclusion (HR, 1.002; 95% CI, 1.001–1.004; P < .001) were associated with mortality/cardiovascular events. Area under receiver operating curve of cystatin C was 0.67 (95% CI, .55–.79) for mortality/cardiovascular event prediction. Biomarkers were not associated with GFR slope. Conclusions: uACR and cystatin C predict all-cause mortality and/or cardiovascular events in PWH independently of mGFR. Abstract : Identifying people with HIV (PWH) at risk for chronic kidney disease, cardiovascular events, and death is crucial. Urine albumin to creatinine ratio and cystatin C predict all-cause mortality and/or cardiovascular events in PWH independently of measured glomerular filtration rate.